2015
DOI: 10.1007/s00404-015-3628-y
|View full text |Cite
|
Sign up to set email alerts
|

Placenta previa: an outcome-based cohort study in a contemporary obstetric population

Abstract: Increased maternal morbidity was noted; however, only those neonatal morbidities associated with preterm delivery occurred in the placenta previa group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 17 publications
1
40
1
2
Order By: Relevance
“…Maternal old age, episodes of antepartum bleeding, fetal non‐cephalic presentation, complete placenta previa, anterior localization of the placenta, placental multiple lacunae (≥4), and uteroplacental hypervascularity were risk factors for massive post‐partum bleeding in our cases. Advanced maternal age is a well‐known risk factor . Also, antepartum bleeding was earlier considered a risk factor associated with post‐partum complications in placenta previa cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal old age, episodes of antepartum bleeding, fetal non‐cephalic presentation, complete placenta previa, anterior localization of the placenta, placental multiple lacunae (≥4), and uteroplacental hypervascularity were risk factors for massive post‐partum bleeding in our cases. Advanced maternal age is a well‐known risk factor . Also, antepartum bleeding was earlier considered a risk factor associated with post‐partum complications in placenta previa cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that massive post-partum hemorrhage can develop in cases of placenta previa, increasing the risk of maternal and neonatal mortality and morbidity. 1,2 In cases of placenta previa, prediction of post-partum blood loss can improve the outcomes of pregnancy and yield information useful in the preparation and management of surgery, including the need for hospital admission, preservation of blood, and timing of the cesarean section (CS). However, although placenta previa is associated with postpartum hemorrhage, massive post-partum bleeding does not always develop.…”
Section: Introductionmentioning
confidence: 99%
“…[New 2018] P A large case-control study found that neonatal morbidities in women with placenta praevia include an increased risk of lower 5-minute Apgar scores, neonatal intensive care unit (NICU) admission, anaemia, respiratory distress syndrome, mechanical ventilation and intraventricular haemorrhage. 64 There is no evidence, however, that neonates born after pregnancies with placenta praevia are more likely to be small for gestational age when compared to non-praevia controls. 65 Evidence The 2016 RCT has found that the administration of betamethasone to women with a singleton pregnancy at risk for late preterm delivery (34 +0 to 36 +5 weeks of gestation) significantly reduces the rate of neonatal respiratory complications.…”
Section: 6mentioning
confidence: 99%
“…In some studies, the increased likelihood of placenta previa has been associated with increased parity at an older maternal age and therefore an increase in previous uterine interventions [8,12]. In 3 cohort studies, advanced maternal age has been reported as the cause of a 1.2-2.7-fold increase in the incidence of placenta previa [13][14][15]. In the current study, advanced maternal age increased the likelihood of placenta previa 2.67-fold.…”
Section: Discussionmentioning
confidence: 99%